(untitled) (AYUSHDHARA, 2024)
Background: In Ayurveda, Galaganda which is characterized by neck swelling is well known. Galaganda is often compared with Goiter which is related with Thyroid disorders. Aaharaja and Viharaja Hetus cause vitiation in Vata, Kapha and Meda. These vitiated Doshas reach the neck and the Nape of the neck gets lodged therein causing swelling in the neck which gradually develops having their respective symptoms. Case Report: In this present study an Indian Female Patient aged 30 years known case of Hyperthyroidism and swelling over the neck for 1 year was treated by Viddha Karma Therapy. Result: The 7 consequent sittings of Viddha Karma led to regression of the size of Thyroid Gland as well as reduction of cervical lymphadenopathy and thus provided relief in signs and symptoms. Also, there were positive significant changes observed in the Thyroid profile and USG reports. This is an effort to find a better and faster treatment for Galaganda by successfully treating the case of Galaganda with Viddha Karma Therapy.